The Influence of Price to Book Value on Capital Structure and Profitability of Health and Pharmaceutical Companies in Indonesia - Suyono Suyono; Sudarno Sudarno; Suhardjo Suhardjo; Yunia Sari; Intan Purnama (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
This study aims to know and analyze the influence of price to book value on capital structure and profitability of health and pharmaceutical companies in Indonesia during the period 2012-2019. The population in this study was 12 companies at health and pharmaceutical sub-sector companies in Indonesia during the period 2012-2019. The sampling technique was done using the purposive sampling method. Based on the sample criteria, there were 8 companies that matched the sample criteria. The data analysis techniques used in this study were descriptive analysis and analysis of Structural Equation Modeling (SEM) with AMOS 21. The results showed (1) PBV variable had a positive and significant influence on capital structure of health and pharmaceutical companies in Indonesia during the period 2012-2019. (2) PBV variable had no significant influence on profitability of health and pharmaceutical companies in Indonesia during the period 2012-2019. (3) Capital structure variable had no significant influence on profitability of health and pharmaceutical companies in Indonesia during the period 2012-2019.